Evaluation of carbon nanoscroll materials for post-combustion CO2 capture. (May 2016) - Daff, Thomas D.; Collins, Sean P.; Dureckova, Hana; Perim, Eric; Skaf, Munir S.; Galvão, Douglas S.; Woo, Tom K.
Abstract: Carbon nanoscrolls are similar to multi-walled carbon nanotubes but constructed from rolled graphene sheets into papyrus-like structures. In this work, molecular simulations are used to evaluate the post-combustion CO2 capture properties of nanoscrolls made of graphene, α-, β-, and γ-graphyne, boron nitride, and three types of carbon nitride. The CO2 uptake capacity, CO2 /N2 selectivity and CO2 working capacity were computed with grand canonical Monte Carlo simulations at conditions relevant to post-combustion CO2 capture. The interlayer spacing of the nanoscrolls was optimized for each property and sheet material. For graphene nanoscrolls, the optimal interlayer spacing of 7.3 Å was identified for both the CO2 uptake and selectivity, while for working capacity the optimal interlayer spacing was determined to be 8.6 Å. It was found that the CO2 uptake capacity of the materials correlated to the density of the sheets from which they were formed. Nanoscrolls made from graphene and boron nitride, which have the highest number of atoms per unit area, also showed the highest CO2 uptakes. At 0.15 bar CO2, 313 K, graphene and boron nitride nanoscrolls exhibited exceptional CO2 uptake capacities of 7.7 and 8.2 mmol/g, respectively, while also exhibiting high CO2 /N2 selectivities of 135 and 153, respectively. Molecular dynamics simulations were used to examine the adsorption kinetics. The simulations showed that an empty graphene nanoscroll with a roll length of 200 Å could adsorb CO2 into the center of the roll within 10 ns. Materials with pores that can allow CO2 to pass through, such as graphynes, showed much faster adsorption times.